Pengaruh Media Bermain Pasir Kinetik Terhadap Aspek Motorik Halus Anak Usia 5-6 Tahun Di TK Pelangi Kasih Siborongborong Kabupaten Tapanuli Utara - Santi Nababan; Winarti Agustina; Hisardo Sitorus (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research was to determine the effect of kinetic sand playing media on the fine motoric aspects of children aged 5-6 years at Pelangi Kasih Siborongborong Kindergarten, North Tapanuli Regency. The method used in this research is a descriptive quantitative research method. The population was all children aged 5-6 years at Pelangi Kasih Siborongborong Kindergarten, North Tapanuli Regency, totaling 54 people and a sample of 20 people was determined using a non-probability sampling technique, namely purposive sampling. Data was collected using a 25-item positive closed questionnaire. The results of data analysis show that there is a positive influence between kinetic sand playing media on the fine motoric aspects of children aged 5-6 years at Pelangi Kasih Siborongborong Kindergarten, North Tapanuli Regency: 1) Analysis requirements test: a) positive relationship test obtained rxy = 0.599 > rtable(=0.05,n=20) = 0.444, thus it is known that there is a positive influence between variable dk=n-2=18)= 2.101, thus there is a significant influence between variable Y ̂=